The calculation of the square root of a complex number $a + ib$ involves solving the equation

$$ (x + iy)^2 = a + ib$$

So far so good. One obtains the equations

$$ 4x^4 -4ax^2 - b^2 = 0, y = b/2x$$

and using the quadratic formula for $x^2$ one gets

$$ x = \pm \sqrt{{a + \sqrt{a^2 + b^2} \over 2}}$$

I am supposed to get

$$ y = \pm \sqrt{- a + \sqrt{a^2 + b^2} \over 2} \cdot \text{sgn}(b)$$

but if I substitute $x$ into $y$ I get

$$ y = {b\over 2x} = \pm {b \sqrt{2} \over 2\sqrt{a + \sqrt{a^2 + b^2}}}$$

What am I doing wrong?

  • $\begingroup$ Possible Duplicate of THIS and THIS. $\endgroup$ – Mark Viola Aug 31 '16 at 19:55

First off, up to a sign (reflected by that $\mbox{sgn }(b)$ factor), the two expressions are equal. You can see this if you multiply the expression you got by $$ \frac{\sqrt{\sqrt{a^2+b^2}-a}}{\sqrt{\sqrt{a^2+b^2}-a}} $$ to get $$ y = \pm \frac{b}{\sqrt{b^2}} \frac{\sqrt{\sqrt{a^2+b^2}-a}}{\sqrt{2}} $$ And of course, since all use of the square root symbol implies the positive square root, $$ \frac{b}{\sqrt{b^2}} = \mbox{sgn }(b) $$

That is, you did everything right, except not trusting your answer.

  1. When $\text{a}\space\wedge\space\text{b}\in\mathbb{C}$: $$\text{a}=\text{b}^2=\left(\Re[\text{b}]+\Im[\text{b}]i\right)^2=\Re^2[\text{b}]-\Im^2[\text{b}]+2\Re[\text{b}]\Im[\text{b}i]$$
  2. Solving $x$: $$y=\frac{\text{b}}{2x}\Longleftrightarrow\text{b}=2xy\Longleftrightarrow x=\frac{\text{b}}{2y}$$
  3. Solving $x$ by substituting $y=x^2$: $$4x^4-4\text{a}x^2-\text{b}^2=0\Longleftrightarrow y=\frac{\text{a}\pm\sqrt{\text{a}^2+\text{b}^2}}{2}\Longleftrightarrow x=\color{red}{\pm}\frac{\sqrt{\text{a}\color{red}{\pm}\sqrt{\text{a}^2+\text{b}^2}}}{\sqrt{2}}$$

So for (3) we find 4 solutions.

And for $\text{sgn}(\text{z})$, when $\text{z}\in\mathbb{C}$ (and $\text{z}\ne0$):



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.